Defining the scope of the European Antimicrobial Resistance Surveillance network in Veterinary medicine (EARS-Vet): a bottom-up and One Health approach. (12th January 2022) - Mader, Rodolphe; ,; Bourély, Clémence; Amat, Jean-Philippe; Broens, Els M; Busani, Luca; Callens, Bénédicte; Crespo-Robledo, Paloma; Damborg, Peter; Filippitzi, Maria-Eleni; Fitzgerald, William; Grönthal, Thomas; et al.
Abstract: Background: Building the European Antimicrobial Resistance Surveillance network in Veterinary medicine (EARS-Vet) was proposed to strengthen the European One Health antimicrobial resistance (AMR) surveillance approach. Objectives: To define the combinations of animal species/production types/age categories/bacterial species/specimens/antimicrobials to be monitored in EARS-Vet. Methods: The EARS-Vet scope was defined by consensus between 26 European experts. Decisions were guided by a survey of the combinations that are relevant and feasible to monitor in diseased animals in 13 European countries (bottom-up approach). Experts also considered the One Health approach and the need for EARS-Vet to complement existing European AMR monitoring systems coordinated by the ECDC and the European Food Safety Authority (EFSA). Results: EARS-Vet plans to monitor AMR in six animal species [cattle, swine, chickens (broilers and laying hens), turkeys, cats and dogs], for 11 bacterial species ( Escherichia coli, Klebsiella pneumoniae, Mannheimia haemolytica, Pasteurella multocida, Actinobacillus pleuropneumoniae, Staphylococcus aureus, Staphylococcus pseudintermedius, Staphylococcus hyicus, Streptococcus uberis, Streptococcus dysgalactiae and Streptococcus suis ). Relevant antimicrobials for their treatment were selected (e.g. tetracyclines) and complemented with antimicrobials of more specific public health interest (e.g. carbapenems). Molecular data detecting the presence of ESBLs, AmpC cephalosporinases and methicillin resistance shall be collected too. Conclusions: A preliminary EARS-Vet scope was defined, with the potential to fill important AMR monitoring gaps in the animal sector in Europe. It should be reviewed and expanded as the epidemiology of AMR changes, more countries participate and national monitoring capacities improve.